Effectiveness of Social Media Platform: A Perspective of Customer Purchase Intention through Social Networking in the Pakistani Context - Mehboob, Irsa; Khan, Mubbsher Munawar (International Review of Management and Marketing, 2020)
The purpose of the study is to explore the association among the social media practices which effect the purchase intention of the consumers in the Pakistani context. The study is helpful for all the practioniers and profit earning organizations as it gives a deep overview of the social media and their practices applied nowadays. The study also examines the mediating role of brand loyalty in these relationships. Paper, as well as electronic questionnaires, were used to collect data from 1000 consumers who use social channels to make a purchase .Structural equation modeling technique (SEM) was applied to test the hypothesized model. The results reflects that all the independent variables have a significant impact on purchase intention (dependent variable) keeping brand loyalty as the mediating variable. The results of the research are beneficial for all those firms and marketers who are targeting the social networking platforms to reach out to their target customers. This study explores the factors of brand loyalty in relation to social media in a unique way, but having few limitations to research such as the use of convenience sampling .Future directions can help the marketers to aim their consumers very precisely implying these social media studies. Keywords: Social Media, Brand Loyalty, Social Networking, Community Engagements, Impression Management, Brand Use, Purchase intention. JEL Classifications: M1, M3 DOI: https://doi.org/10.32479/irmm.10449